Associations Between Vitamin K and Suicide Attempts in Patients with Depression: A Case-Control Study [Letter] - Wang S; Wang X; Jiang X (Dove Medical Press, 2024)
Song Wang,1,* Xi Wang,2,* Xiaolian Jiang1 1West China School of Nursing/West China Hospital, Sichuan University, Chengdu, Sichuan, 610041, People’s Republic of China; 2School of Nursing, Bengbu Medical University, Bengbu, Anhui, 233030, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiaolian Jiang, West China School of Nursing/West China Hospital, Sichuan University, No. 37, Guoxue Lane, Wuhou District, Chengdu, Sichuan, 610041, People’s Republic of China, Email jiang_xiaolian@126.com; jangxaolianhl@163.com